Analisis Pengaruh Komitmen Organisasi Terhadap Semangat Kerja Pegawai Kantor Dinas Pertanian Kota Bima - Wardimansyah Wardimansyah; Wulandari Wulandari (Journal MISSY (Management and Business Strategy), 2020)
This study aims to determine the effect of organizational commitment on employee morale in the Agriculture Office of the City of Bima. The criteria set by the researcher as the sample in this study were the employees of the Civil Service Office (ANS) at the main service with a total of 61 people using purposive sampling technique, namely the method of selecting samples based on certain criteria. Based on the results of data processing using SPSS version 23.0, the following results were obtained: This type of research is associative with a population of 52 employees based on the Slovin formula. The constant value is positive at 22.559 and the oefficient of organizational commitment variable is 0.378, so the regression equation can be written: Y = 22.559 + 0.378X, and the correlation coefficient (R) = 0.222. This means that the variable organizational commitment (X) in explaining the morale variable (Y) is in the low category. R Square value of 0.049. This means that the contribution of the organizational commitment variable (X) to morale (Y) is 0.49%, while 46.5% is influenced by variables outside of this research model. For the t-test, two parties reject the alternative hypothesis (Ha) which states that organizational commitment has no effect on morale in the agricultural department of the city of Bima (H0 is accepted).